Performance based funding from the Global Fund to fight AIDS, Tuberculosis and Malaria : a case study of Grant SAF-304-GO4-H in the Western Cape, South Africa - Naimak, Trude Holm (Aids and Society Research Unit, 2014)
Includes bibliographical references.